Education and employment outcomes in Ghana through the lens of the capability approach [Scolarisation et emploi au Ghana à travers la lunette de l’approche des capabilités] - Sarkodie, A.O.; Agyei-Mensah, S.; Anarfi, J.K.; Bosiakoh, T.A. (Etude de la Population Africaine / Union for African Population Studies, 2014)
Existing literature on education and employment confirms that in Ghana educational qualification largely influences the type of work. Through the lens of the Capability Approach, which sees human development in terms of the expansion of freedoms and opportunities, this paper identifies, for a cross-section of Ghanaians, the array of employment opportunities between and within education endowments. “Between endowments” refers to differentials in opportunities for individuals with different levels of educational qualifications, while “within endowments” considers the differentials for individuals with the same level of education. The source of data is the 2005/06 Ghana Living Standard Survey (GLSS5). Results show that education is not enough to erase inequalities. Multinomial regression analysis demonstrates that functionings differ according to the individual’s context, household and personal conversion factors. This is explained by inequalities in the requirements for a particular job (between educational endowments) and by job accessibility due to personal characteristics (within educational endowments). © 2014, Union for African Population Studies. All rights reserved.
Keywords: Capabilities; Conversion factors; Education; Employment; Ghana